2005
DOI: 10.1097/01.sap.0000170530.51470.1a
|View full text |Cite
|
Sign up to set email alerts
|

Delaying the Reverse Sural Flap Provides Predictable Results for Complicated Wounds in Diabetic Foot

Abstract: Defective wounds in diabetic foot are difficult to manage. Several studies reported the use of reverse sural flap in a small number of patients with varying success. We presented our experience with the reverse sural island flap (RSIF) in a series of 37 patients associated with diabetic foot using the delay procedure. The ages of the patients ranged between 36 and 73 years. We did not perform angiographic evaluation to determine the existence of vascular connections between the branches of the peroneal and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 19 publications
0
52
0
1
Order By: Relevance
“…Other authors do not tunnel the flap under the skin due to fear of compression of the fatty pedicle against the skin especially in the postoperative phase when more swelling develops [13]. Other modifications to increase size include delaying [14][15][16] a wider than usual pedicle [17], supercharging [18], and harvesting a midline cuff of the gastrocnemius muscle with the flap [19]. Techniques without proximal extension of the flap such modifications included exteriorizing the pedicle [20], mobilizing the peroneal perforator in the intermuscular septum [6], and cross-leg sural flap [21].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors do not tunnel the flap under the skin due to fear of compression of the fatty pedicle against the skin especially in the postoperative phase when more swelling develops [13]. Other modifications to increase size include delaying [14][15][16] a wider than usual pedicle [17], supercharging [18], and harvesting a midline cuff of the gastrocnemius muscle with the flap [19]. Techniques without proximal extension of the flap such modifications included exteriorizing the pedicle [20], mobilizing the peroneal perforator in the intermuscular septum [6], and cross-leg sural flap [21].…”
Section: Discussionmentioning
confidence: 99%
“…Seven to 15 days later, the flap is elevated again and transposed into the defect site. In 2005, three authors proposed a distally-based sural flap delay procedure [11][12][13] . Among them, Erdmann et al 13 described a sural flap delay procedure to avoid flap necrosis in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…For such patients, they suggested that a surgical delay procedure should be considered 9 . The advantage of the delay procedure is that it improves flap survivability in patients with significant medical comorbidities [9][10][11][12][13] . Accordingly, we treated seven high-risk patients with soft tissue defects of the lower extremity by using a delayed reverse sural flap, and the results were excellent.…”
mentioning
confidence: 99%
“…Several studies show that in comorbid patient populations, utilizing a staged application of the sural flap leads to greater flap viability. 16,17 The staging procedure helps improve venous outflow, which is the limiting factor in large sural flaps, especially in comorbid patients. Delaying the flap causes local vascular dilation, leading to hyperplasia and an increase in the capacity of the local circulatory system.…”
Section: Discussionmentioning
confidence: 99%